British Society for Rheumatology Biologics Register. (7th October 2003) - Silman, A; Symmons, D; Scott, D G I; Griffiths, I
Abstract : The British Society for Rheumatology (BSR) established a register of patients newly treated with biological agents, the BSR Biologics Register (BSRBR), which became active in January 2002. The goal is to register all patients in the United Kingdom with rheumatic diseases, newly starting treatment with these agents and to follow them up to determine the incidence of any short and long term hazards to health. The Register is also recruiting a comparison cohort of patients with rheumatoid arthritis treated with standard disease modifying antirheumatic drugs to determine the relative contributions of disease factors and other treatments apart from biological agents on any risks observed.